2017
DOI: 10.1302/2046-3758.61.bjr-2016-0081
|View full text |Cite
|
Sign up to set email alerts
|

Measuring hip muscle strength in patients with femoroacetabular impingement and other hip pathologies

Abstract: ObjectivesThe aim of this study was to systematically review the literature on measurement of muscle strength in patients with femoroacetabular impingement (FAI) and other pathologies and to suggest guidelines to standardise protocols for future research in the field.MethodsThe Cochrane and PubMed libraries were searched for any publications using the terms ‘hip’, ‘muscle’, ‘strength’, and ‘measurement’ in the ‘Title, Abstract, Keywords’ field. A further search was performed using the terms ‘femoroacetabular’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
(64 reference statements)
0
30
0
Order By: Relevance
“…Systematic reviews included in the evidence summary consistently report lower muscle strength for hip adduction, abduction, flexion, internal rotation and external rotation in individuals with hip-related pain compared with individuals without pain 8 9 19. However, there is conflicting evidence whether extension strength deficits are found in this population (online supplementary appendix).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews included in the evidence summary consistently report lower muscle strength for hip adduction, abduction, flexion, internal rotation and external rotation in individuals with hip-related pain compared with individuals without pain 8 9 19. However, there is conflicting evidence whether extension strength deficits are found in this population (online supplementary appendix).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in neuromuscular function of the hip are associated with intra‐articular hip joint pathology. Recent systematic reviews (Diamond et al, ; Freke et al, ; Mayne et al, ) and research studies have examined physical impairments associated with FAI syndrome, acetabular labral pathology and chondropathology, and have found impaired hip range of motion (Kemp et al, ; Diamond et al, ), reduced hip muscle strength (Casartelli et al, ; Harris‐Hayes et al, ; Mendis et al, ; Kemp et al, ; Nepple et al, ; Diamond et al, ), impaired functional task performance (Hatton et al, ; Bagwell et al, ; Charlton et al, ; Kemp et al, ; Samaan et al, ), and altered gait biomechanics (Kennedy et al, ; Brisson et al, ; Hunt et al, ; Ng et al, ). With respect to hip muscle size, previous research has investigated size of the gluteal muscles in patients with chronic hip joint pain (Mastenbrook et al, ) and of the individual hip flexor muscles in patients with acetabular labral pathology (Mendis et al, ); however, no research to date has investigated the individual hip abductor, hip extensor, or hip external rotator muscles in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the differences in joint loading may provide a better strategy for athletic conditioning, training program, or nonsurgical management 5,10,45. As Mayne and associates (2017) recently pointed out that knowledge pertaining to hip muscle strength associated with FAI patients is very limited 49. Although previous studies reported joint kinematics and kinetics associated with cam FAI, none of the studies determined hip contact forces from musculoskeletal modelling, to compare joint loading between a cohort of FAI and CON participants.…”
mentioning
confidence: 99%